PENGARUH STRUKTUR KEPEMILIKAN, LIKUIDITAS DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN UTANG SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR TEKSTIL DAN GARMEN PERIODE 2022-2024 - Jama, Felensia Jati Ata; Pramitasari, Triska Dewi; Sari, Lita Permata (Fakultas Ekonomi dan Bisnis, 2025)
The purpose of this study is to determine the effect of ownership, liquidity, and profitability structure on company value with debt policy as an intervening variable in manufacturing companies in the textile sub-sector and garment for the 2022-2024 period. The population in this study was all manufacturing companies in the textile and garment sub-sector for 2022-2024 in 25 companies. The sampling technique in this study used purposive sampling so that eleven samples were obtained for data analysis. Data Analysis and Hypothesis Testing used the Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results of the hypothesis test of the direct effect using the Smart PLS 3.0 application show that the structure of ownership has a negative but not significant effect on debt policy, liquidity has a significant negative effect on debt policy, profitability has a positive but not significant effect on debt policy, ownership structure has a positive but not significant effect on company value, liquidity has a significant positive effect on company value, profitability has a negative but not significant effect on company value, debt policy has a positive but not significant effect on company value. The results of the hypothesis test of the influence did not directly show that the structure of ownership had a negative but not significant effect on the company’s value through debt policy, liquidity had a negative but not significant effect on the value of the company through debt policy, profitability had a positive but not significant effect on the company’s value through debt policy.